Preferensi Rayap (Isoptera: Termitidae) Pada Berbagai Tonggak di Kawasan Cagar Alam Bantarbolang Pemalang Jawa tengah - Risty Deviriani; Imam Widhiono; Hery Pratiknyo (Fakultas Biologi Universitas Jenderal Soedirman, 2019)
Termite family Termitidae is a type of wood-eating termites, humus, or materials consisting of cellulose. This familia termite has a role in helping the ecosystem as a decomposer by destroying wood or other organic material and returning it as nutrients to the soil. Preference or prefer food sources that exist in the environment, influential in supporting the development of termites. The purpose of this study is to find out the type of wood that is a food preference for termites and species of the termite family Termitidae in the Bantarbolang Pemalang Nature Reserve in Central Java. This research was conducted at the Bantarbolang Nature Reserve located in the Kebon Gede Village Area, Bantarbolang District, Pemalang Regency, Central Java. The research method used survey method with termite sampling technique on the milestone paying attention to the depth of entering the forest (0 m, 50 m, 100 m, 150 m and 200 m) from the edge of the forest and paying attention to the age of the post since cutting trees. Termite species were taken on teak (Tectona grandis), Wangkal (Albizia procera), and Mahoni (Switenia marcrophilla) stakes found in areas of 0 m to 200 m. The data obtained were analyzed using analysis of variance (ANOVA). The termites taken are inserted into vial bottles containing 70% alcohol and all termite colonies are counted to determine the number of individual termites. Measurement of environmental parameters include temperature, humidity, soil pH, canopy cover and light intensity. The results obtained by a species of termite Macrotermes gilvus familia Termitidae. The results of data analysis using the f test on teak (Tectona grandis), Wangkal (Albizia procera), and Mahoni (Switenia marcrophilla) milestones show that the significance value is > 0.05, which means the age of the milestone and the distance of the milestone from the forest edge do not affect significantly to the presence of Macrotermes gilvus termites on these wooden posts. The conclusion of this study is that the preferences of Macrotermes gilvus termites for various wooden stakes in the Bantarbolang Nature Reserve are not influenced by the age of the stakes and the distance of the wooden stakes from the edge of the forest.